The Mount Sinai international enhancement of social work leadership program: The past and the future. (3rd July 2018) - Gordon, Elisa; Green, Karen; Whitwam, Louisa; Epstein, Irwin; Bernstein, Susan
ABSTRACT: Developed in 1988, the Mount Sinai International Enhancement of Social Work Leadership Program brings 4-6 social workers from several countries each year to the Mount Sinai Hospital in New York City, where they meet with leaders from the hospital, community based organizations and graduate schools of social work, to enhance their leadership ability, strengthen management and research skills, and build upon global social work relationships. This article reviews the results of a survey conducted in 2016 to assess whether the visiting scholars met established learning objectives of the Program. Survey outcomes, presented in quantitative and qualitative terms, show positive results, and the scholars reported that the Program was extremely beneficial. The Program is viewed through the lens of two select adult learning theories: Social Learning Theory, which incorporates collaboration and learning from others, and Transformative Learning Theory, which is comprised of self-reflection and individualized learning. The inclusion of these theories in the implementation of the Program will be discussed. An analysis of the survey's outcomes, through pre- and post-Program participation and learning, facilitates assessment of potential programmatic adjustments to help evaluate long-term viability of the Program and potential duplication by other academic medical centers.